Con Mine tower, Yellowknife, Northwest Territories, Canada -- photograph ... - Seale, Linda N. (University of Alberta Library, 2012)
The Con Mine tower or Robertson Headframe was a landmark in Yellowknife, Northwest Territories and was visible from planes landing at the airport, and from Great Slave Lake. It marks the site of the Con, or Cominco, gold mine, first staked in 1935 and productive until 2003. The tower was demolished in October 2016, being too expensive to maintain. The mine shafts are a potential source of geothermal energy which could heat half of the city. A memorandum of understanding was signed in June 2011 between the City of Yellowknife and Corix Utilities. Photograph taken March 2012 from Rat Lake : description updated October 2016. ...